Inhibition of carbonic anhydrase prevents the Na /H exchanger 1-dependent slow force response to rat myocardial stretch - Vargas, Lorena Alejandra (2013)
Myocardial stretch is an established signal that leads to hypertrophy. Myocardial stretch induces a first immediate force increase followed by a slow force response (SFR), which is a consequence of an increased Ca2+ transient that follows the NHE1 Na+/H+ exchanger activation. Carbonic anhydrase II (CAII) binds to the extreme COOH terminus of NHE1 and regulates its transport activity. We aimed to test the role of CAII bound to NHE1 in the SFR. The SFR and changes in intracellular pH (pHi) were evaluated in rat papillary muscle bathed with CO2/HCO3− buffer and stretched from 92% to 98% of the muscle maximal force development length for 10 min in the presence of the CA inhibitor 6-ethoxzolamide (ETZ, 100 μM). SFR control was 120 ± 3% (n = 8) of the rapid initial phase and was fully blocked by ETZ (99 ± 4%, n = 6). The SFR corresponded to a maximal increase in pHi of 0.18 ± 0.02 pH units (n = 4), and pHi changes were blocked by ETZ (0.04 ± 0.04, n = 6), as monitored by epifluorescence. NHE1/CAII physical association was examined in the SFR by coimmunoprecipitation, using muscle lysates. CAII immunoprecipitated with an anti-NHE1 antibody and the CAII immunoprecipitated protein levels increased 58 ± 9% (n = 6) upon stretch of muscles, assessed by immunoblots. The p90RSK kinase inhibitor SL0101–1 (10 μM) blocked the SFR of heart muscles after stretch 102 ± 2% (n = 4) and reduced the binding of CAII to NHE1, suggesting that the stretch-induced phosphorylation of NHE1 increases its binding to CAII. CAII/NHE1 interaction constitutes a component of the SFR to heart muscle stretch, which potentiates NHE1-mediated H+ transport in the myocardium.